2019
DOI: 10.1128/aac.00886-19
|View full text |Cite|
|
Sign up to set email alerts
|

Essential Role for the Phosphatidylinositol 3,5-Bisphosphate Synthesis Complex in Caspofungin Tolerance and Virulence in Candida glabrata

Abstract: Increasing resistance of the human opportunistic fungal pathogen Candida glabrata toward the echinocandin antifungals, which target the cell wall, is a matter of grave clinical concern. Echinocandin resistance in C. glabrata has primarily been associated with mutations in the β-glucan synthase-encoding genes C. glabrata FKS1 (CgFKS1) and CgFKS2. This notwithstanding, the role of the phosphoinositide signaling in antifungal resistance is just beginning to be deciphered. The phosphatidylinositol 3,5-bisphosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…4 A recent study in C glabrata emphasized the importance of phosphatidylinositol 3,5-bisphosphate, a low abundance lipid molecule, in the maintenance of cell wall chitin, caspofungin tolerance, survival within host cells, and virulence. 26 Another study in C auris , an emerging pathogenic fungus, showed higher abundance of sphingoid bases in its plasma membrane, including higher levels of phytosphingosine compared to C albicans strains. 27 This study also suggests that increased sphingolipid content may be related to increased resistance to antifungals typical of C auris.…”
Section: Role Of Plasma Membrane Lipids In Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…4 A recent study in C glabrata emphasized the importance of phosphatidylinositol 3,5-bisphosphate, a low abundance lipid molecule, in the maintenance of cell wall chitin, caspofungin tolerance, survival within host cells, and virulence. 26 Another study in C auris , an emerging pathogenic fungus, showed higher abundance of sphingoid bases in its plasma membrane, including higher levels of phytosphingosine compared to C albicans strains. 27 This study also suggests that increased sphingolipid content may be related to increased resistance to antifungals typical of C auris.…”
Section: Role Of Plasma Membrane Lipids In Drug Resistancementioning
confidence: 99%
“…26 Another study in C auris , an emerging pathogenic fungus, showed higher abundance of sphingoid bases in its plasma membrane, including higher levels of phytosphingosine compared to C albicans strains. 27 This study also suggests that increased sphingolipid content may be related to increased resistance to antifungals typical of C auris. The authors mention that these lipids are important for the assembly of membrane platforms containing drug efflux pumps.…”
Section: Role Of Plasma Membrane Lipids In Drug Resistancementioning
confidence: 99%
“…It has been previously shown that phosphoinositide signaling pathways have a role in resistance development to azoles by regulating various cellular processes such as protein trafficking, autophagy, cell cycle progression and hyphal morphogenesis (Choudhary et al . 2019 ). Additionally, phosphatidylinositol-4-phosphate is vital for the trafficking of the major multidrug transporter Cdr1, to the plasma membrane (Ghugtyal et al .…”
Section: Echinocandinsmentioning
confidence: 99%
“…One study showed that the CgFab1 , CgVac7, and CgVac14 signaling components for phosphatidylinositol 3,5-bisphosphate ( PI (3,5) P2 ) genes are important for biofilm formation, cell survival, and virulence of C. glabrata , since strains with mutations in these genes tend to have a defective cell wall and because the impaired vacuolar functions and biofilm formation observed in vitro was diminished [ 203 ].…”
Section: Biofilm Formationmentioning
confidence: 99%